Flipped Learning for Enhancing Intensive Reading Comprehension via Google Classroom: A Quasi-Experimental Study - Heryatun, Yayu; Amaliah, Hanifah; Rohmawati , Cucum (FOSTER: Journal of English Language Teaching, 2025)
This research delved into the efficacy of the flipped learning strategy in enhancing students' intensive reading comprehension and explored their responses to its implementation via Google Classroom. A quasi-experimental study involved 66 seventh-grade students from a state junior high school in Cilegon, strategically divided into an experimental group adopting flipped learning and a control group utilizing traditional scientific methods. Data, gathered through pre-tests and post-tests to gauge reading comprehension and questionnaires to capture student perspectives, were analyzed using SPSS. An independent sample t-test revealed that the experimental group achieved significantly higher post-test scores (80.06) compared to the control group (74.27), underscoring the superior effectiveness of flipped learning in boosting reading comprehension. Furthermore, the questionnaire results showed a predominantly positive student outlook on leveraging Google Classroom within this flipped pedagogical framework. Consequently, this study concludes that flipped learning, powerfully supported by Google Classroom, stands as a robust and well-received strategy for refining students' intensive reading comprehension